Microbial Ecology of Sulfur Biogeochemical Cycling at a Mesothermal Hot Spring Atop Northern Himalayas, India - Nagar, Shekhar; Talwar, Chandni; Motelica-Heino, Mikael; Richnow, Hans-Hermann; Shakarad, Mallikarjun; Lal, Rup; Negi, Ram Krishan (Frontiers in Microbiology, 2022)
Sulfur Related Prokaryotes (SRP) residing in hot spring present good opportunity for exploring the limitless possibilities of integral ecosystem processes. Metagenomic analysis further expands the phylogenetic breadth of these extraordinary sulfur metabolizing microorganisms, as well as their complex metabolic networks and syntrophic interactions in environmental biosystems. Through this study, we explored and expanded the microbial genetic repertoire with focus on sulfur cycling genes through metagenomic analysis of sulfur (S) contaminated hot spring, located at the Northern Himalayas. The analysis revealed rich diversity of microbial consortia with established roles in S cycling such as Pseudomonas, Thioalkalivibrio, Desulfovibrio and Desulfobulbaceae (Proteobacteria). The major gene families inferred to be abundant across microbial mat, sediment and water were assigned to Proteobacteria as reflected from the RPKs (reads per kilobase) categorized into translation and ribosomal structure and biogenesis. Analysis of sequence similarity showed conserved pattern of both dsrAB genes (n=178) retrieved from all metagenomes while other sulfur disproportionation proteins were diverged due to different structural and chemical substrates. The diversity of sulfur oxidizing bacteria (SOB) and sulfate reducing bacteria (SRB) with conserved (r)dsrAB suggests for it to be an important adaptation for microbial fitness at this site. Here, (i) the oxidative and reductive dsr evolutionary time scale phylogeny, proved that the earliest (not first) dsrAB proteins belong to anaerobic Thiobacillus with other (rdsr) oxidizers, also we confirm that (ii) SRBs belongs to δ-Proteobacteria occurring independent LGT of dsr genes to different and few novel lineages. Further, the structural prediction of unassigned DsrAB proteins confirmed their relatedness with species of Desulfovibrio (TM score= 0.86; 0.98; 0.96) and Archaeoglobus fulgidus (TM score= 0.97; 0.98). We proposed that the genetic repertoire might provide the basis of studying time scale evolution and horizontal gene transfer of these genes in biogeochemical S cycling.